2021
DOI: 10.14710/ijred.2021.34138
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Optimization of Non-Catalytic In-Situ Biodiesel Production from Rice Bran Using Response Surface Methodology Historical Data Design

Abstract: Rice bran oil (RBO)is claimed to be a potential feedstock for biodiesel production. Non-catalytic in-situ biodiesel production from a low-cost feedstock (rice bran) using subcritical ethanol-water mixture was investigated in this study. The influence of four independent variables, i.e., addition of co-solvent, ethanol concentration, temperature, and time of reactions, on the yield of biodiesel was examined. The results showed that the most effective co-solvent wasethyl acetate and the optimum ethanol concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Biofuels typically depend on government subsidies and policy support to compete with conventional fuels. As a result of fluctuations in oil prices, the cost-competitiveness of biofuels might be affected, which can result in unclear market prospects [266]- [268]. In addition, the biofuel industry requires significant advancements in both technology and infrastructure to improve efficiency and reduce costs [269], [270].…”
Section: ) Biofuel-based Energy Forecastingmentioning
confidence: 99%
“…Biofuels typically depend on government subsidies and policy support to compete with conventional fuels. As a result of fluctuations in oil prices, the cost-competitiveness of biofuels might be affected, which can result in unclear market prospects [266]- [268]. In addition, the biofuel industry requires significant advancements in both technology and infrastructure to improve efficiency and reduce costs [269], [270].…”
Section: ) Biofuel-based Energy Forecastingmentioning
confidence: 99%
“…Apalagi para pengusaha tahu mempunyai kepercayaan terhadap tahu yang akan dipasarkan, agar para pelaku usaha retail terjamin ketersediaan barangnya. Berdasarkan dari sudut pandang toko kacang kedelai, toko kacang kedelai diperkirakan berdirinya industri tahu menyebabkan peningkatan penjualan kedelai secara signifikan, yang pada akhirnya memberikan kontribusi signifikan terhadap keuntungan sektor tersebut (Baugh, 2018;Blau, 2019;Cornaggia, 2022;Kuśnierz-Krupa, 2019;Neuman, 2018;Niehaus, 2020;Vita, 2020;Zullaikah, 2021).…”
Section: Pengaruh Industri Tahu Bungkeng Terhadap Masyarakat Sekitarunclassified
“…Indeed, heterogeneous acid catalysts such as oxides of metal, heteropoly acids, ionic liquids (ILs), sulfonic-acid-functionalized catalysts, zeolites, and others are considered as popular catalysts in producing biodiesel; their classification is depicted in Figure . However, these described catalytic systems possess one or more of these three drawbacks: poor conversion, high cost, and catalyst toxicity. , A previous study has shown that heteropolyacids are very effective acidic catalysts for chemical processes; however, straight heteropolyacids are readily solvable in polar environments, rendering recovery problematic, in addition to having a limited surface. , So, to prevent such penalties, the heteropolyacids should be encapsulated inside porous frameworks. , …”
Section: Introductionmentioning
confidence: 99%
“…45 However, these described catalytic systems possess one or more of these three drawbacks: poor conversion, high cost, and catalyst toxicity. 46,47 A previous study has shown that heteropolyacids are very effective acidic catalysts for chemical processes; 48 however, straight heteropolyacids are readily solvable in polar environments, rendering recovery problematic, in addition to having a limited surface. 49,50 So, to prevent such penalties, the heteropolyacids should be encapsulated inside porous frameworks.…”
Section: Introductionmentioning
confidence: 99%